Proceedings of the Ocean Drilling Program, 142 Scientific Results 1995
DOI: 10.2973/odp.proc.sr.142.112.1995
|View full text |Cite
|
Sign up to set email alerts
|

Trace Element Determinations by X-Ray Fluorescence Analysis: Advantages, Limitations, and Alternatives

Abstract: A statistical study of data files obtained by repeated X-ray fluorescence analyses (XRF) of many major and 13 trace components in 20 reference materials was conducted aboard JOIDES Resolution. The results indicate that XRF is excellent for determining most main elements in many rocks and of some trace elements (for instance Nb, Y, Sr and Rb) even at low concentrations (4-10 ppm) and that XRF data obtained aboard ship are of the same quality as XRF data reported from land-based laboratories.Other trace componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…From the collected spectra, we were able to identify some major elements in the Marcellus shale notably Al, Ca, Ti, Si, Mg and C. These elements corroborated with the previous findings of Heron et al [11], Gladney et al [12], and Boström and Bach [13] on rock characterization using neutron induced capture gamma ray spectroscopy, x-ray fluorescence, and inductively coupled plasma optical emission spectrometry. Lines with spectral interference, and resonance lines were mostly avoided and preference was given to non-resonance lines [14].…”
Section: Spectral Lines Selectionsupporting
confidence: 89%
“…From the collected spectra, we were able to identify some major elements in the Marcellus shale notably Al, Ca, Ti, Si, Mg and C. These elements corroborated with the previous findings of Heron et al [11], Gladney et al [12], and Boström and Bach [13] on rock characterization using neutron induced capture gamma ray spectroscopy, x-ray fluorescence, and inductively coupled plasma optical emission spectrometry. Lines with spectral interference, and resonance lines were mostly avoided and preference was given to non-resonance lines [14].…”
Section: Spectral Lines Selectionsupporting
confidence: 89%
“…(1972, 1978), Church (1981), Robinson and Bennett (1981), Verma et al. (1992), Cantagrel and Pin (1994), Boström and Bach (1995), Han et al. (1999), Makishima et al.…”
Section: Databases and Analytical Methodsmentioning
confidence: 99%
“…Individual concentration values for Ni and Cr in ten of these RMs were compiled from the following references: Steele et al (1972Steele et al ( , 1978, Church (1981), Robinson and Bennett (1981), Verma et al (1992), Cantagrel and Pin (1994), Boström and Bach (1995), Han et al (1999), Makishima et al (2002), Naqvi et al (2002), Féménias et al (2003), Hoang and Uto (2003), Kelley et al (2003), Haase et al (2004), Ichiyama and Ishiwatari (2005), Ionov et al (2005), Manikyamba et al (2005), Ishizuka et al (2006), Kurosawa et al (2006), Makishima and Nakamura (2006), Ujiie-Mikoshiba et al (2006), and Hastie et al (2007) as well as from two internet addresses (http://riodb.ibase.aist.go.jp/ and http://georem.mpch. mainz.gwdg.de).…”
Section: Databases and Analytical Methodsmentioning
confidence: 99%
“…Previous studies of Hole 504B rocks revealed that chemical data sets of various laboratories differ significantly because of different analytical accuracies and precisions (Dick, Erzinger, Stokking, et al, 1992, andBoström andBach, 1995, for a discussion). We therefore carefully tested our data with the reference data from Govindaraju (1994) and with data from other laboratories to ensure proper analytical accuracy.…”
Section: Sample Preparation and Analytical Proceduresmentioning
confidence: 99%